Direct vitamin D3 actions on rhesus macaque follicles in three-dimensional culture: assessment of follicle survival, growth, steroid and anti-Müllerian hormone production - Xu, Jing (Fertil Steril, 2016)
OBJECTIVE: To investigate the direct actions of active 1,25-dihydroxy vitamin D3 (VD3) upon primate follicular development at specific stages of folliculogenesis. DESIGN: Secondary preantral follicles were isolated from rhesus monkeys ovaries, encapsulated in alginate, and cultured for 40 days. Follicles were randomly assigned to experimental groups of control, low-dose VD3 (LVD3; 25 pg/ml), and high-dose VD3 (HVD3; 100 pg/ml). SETTING: National primate research center. ANIMALS: Adult, female rhesus macaques (Macaca mulatta). INTERVENTION(S): None. MAIN OUTCOME MEASURE(S): Follicle survival and growth, as well as oocyte size were assessed. Progesterone (P4), androstenedione (A4), estradiol (E2), and anti-Müllerian hormone (AMH) concentrations in culture media were measured. RESULTS: Compared with the control group, LVD3 increased preantral follicle survival at week 2 by > 66%, while HVD3 increased antral follicle diameters at week 5. Follicles with diameters ≥ 500 µm at week 5 were categorized as fast-growing follicles. Higher percentages of fast-growing follicles were obtained following HVD3 treatment. Although P4, A4, and E2 production by antral follicles were not altered by VD3, AMH concentrations were 36% higher in LVD3 group relative to controls at week 5. Oocytes with larger diameters were retrieved from antral follicles developed in both LVD3 and HVD3 groups compared with controls. CONCLUSION: The addition of low-dose VD3 increased preantral follicle survival and maintained AMH production by antral follicles, while high-dose VD3 improved antral follicle growth. VD3 supplement promoted oocyte growth in in vitro-developed follicles. Direct actions of VD3 on the primate follicle appear to be both dose- and stage-dependent.